OED Review of the Poverty Reduction Strategy Process : Cambodia Case Study - Operations Evaluation Department (World Bank, Washington, DC, 2014)
This report analyzes the experience of Cambodia with the Poverty Reduction Strategy Paper (PRSP) process3. The focus of the report is on evaluating the performance of the World Bank in supporting the PRSP initiative, not on appraising the authorities policies. Given the early stage of the PRS Process, with the document only formally launched by government in March 2003, the report focuses on the process of PRSP formulation in Cambodia and the genesis of the implementation phase. The report is structured as follows: the remainder of section one provides brief background information about Cambodia. Section two offers an appraisal of the PRSP formulation process and of the document itself, focusing on aspects relevant to an evaluation of the World Bank s role. Section three assesses the World Bank s support to the process. Section four summarizes the main points of the assessment and attempts to draw lessons of more general applicability.